Improved method for quantification of regional cardiac function in mice using phase-contrast MRI. - Dall'Armellina, E; Jung, B; Lygate, C; Neubauer, S; Markl, M; Schneider, J (2012)
Phase-contrast magnetic resonance imaging is a technique that allows for characterization of regional cardiac function and for measuring transmural myocardial velocities in human hearts with high temporal and spatial resolution. The application of this technique (also known as tissue phase mapping) to murine hearts has been very limited so far. The aim of our study was to implement and to optimize tissue phase mapping for a comprehensive assessment of murine transmural wall motion. Baseline values for regional motion patterns in mouse hearts, based on the clinically used American Heart Association's 17-segment model, were established, and a detailed motion analysis of mouse heart for the entire cardiac cycle (including epicardial and endocardial motion patterns) is provided. Black-blood contrast was found to be essential to obtain reproducible velocity encoding. Tissue phase mapping of the mouse heart permits the detailed assessment of regional myocardial velocities. While a proof-of-principle application in a murine ischemia-reperfusion model was performed, future studies are warranted to assess its potential for the investigation of systolic and diastolic functions in genetically and surgically manipulated mouse models of human heart disease.